The community pillars project: engaging survivors as cross- cultural facilitators in Aotearoa/ New Zealand - Mortensen, Annette; O'Connor, Seini; Hibtit, Aklilu; Sheikh, Julia; Alkass, Elizabeth; Arshad, Ruzaika; Behayaa, Huthami; Dawson, Priscilla; Misghina, Ghirmai; Ntawe, Marguerite; Sumanasiri, Ven.; Tun, Salma Khin; et al. (Torture Journal, 2023)
Introduction: Communities who have fled torture and persecution in their home countries can find it difficult to access services in new cultural settings. Past research has shown that it is helpful to provide cultural bridging services to form a connection between locally-trained professionals and newly relocated communities. Method: This article presents, from a practitioner’s perspective, a case example of cultural bridging involving a pilot programme to train torture survivors and former refugees to become Cross-Cultural Facilitators supporting mental health services for displaced communities. Results: The Cross-Cultural Facilitator role has become an integral part of the case example agency’s services. Internal agency reviews of the Cross-Cultural Facilitators’ work shows that they have been continuing to operate successfully through challenging times, including the many societal disruptions and stressors entailed in the Covid-19 pandemic. The agency has also gathered notable anecdotal evidence that the pilot training programme has been positively impactful and supportive not only for the Cross-Cultural Facilitators but for the communities they serve. Discussion: Healthcare workers and civil society organisations have an important role to play in supporting survivors to engage in this form of cultural facilitation aimed at addressing the consequences of traumatic experiences at a community level. In doing so, they must balance efforts to empower survivors and former refugees to participate as agents of change with a duty of care not to push individuals into roles or settings that may diminish their own wellbeing.